Impact of oral health on health-related quality of life: a cross-sectional study - Zucoloto, Miriane Lucindo [UNESP]; Maroco, Joao; Duarte Bonini Campos, Juliana Alvares [UNESP] (Biomed Central Ltd, 2016)
Background: Despite the consensus regarding the existence of a relationship between '' impacts on oral health '' and '' health-related quality of life '', this relationship, considering the latent nature of these variables, is still poorly investigated. Thus, we performed this study in order to determine the magnitude of the impacts of oral health, demographic and symptom/clinical variables on the health-related quality of life in a Brazilian sample of dental patients. Methods: A total of 1,007 adult subjects enrolled in the School of Dentistry of Sao Paulo State University (UNESP) - Araraquara Campus for dentistry care between September/2012 and April/2013, participated. 72.4 % were female. The mean age was 45.7 (SD = 12.5) years. The Oral Health Impact Profile (OHIP-14) and the Short Form Health Survey (SF-36) were used. The demographic and symptom/clinical variables collected were gender, age, economic status, presence of pain and chronic disease. The impact of studied variables on health-related quality of life were evaluated with a structural equation model, considering the factor Health as the central construct. The fit of the model was first analyzed by the evaluation of the goodness of fit indices (chi(2)/df <= 2.0, CFI and TLI >= 0.90 and RMSEA < 0.10) and the evaluation of the variables' impact over health-related quality of life was based on the statistical significance of causal paths (beta), evaluated by z tests, for a significance level of 5 %. Results: We observed adequate fit of the model to the data (chi(2)/df = 3.55; CFI = 0.95; TLI = 0.94; RMSEA = 0.05). The impacts on oral health explained 28.0 % of the variability of the health-related quality of life construct, while the total variance explained of the model was 39.0 %. For the demographic and symptom/clinical variables, only age, presence of pain and chronic disease showed significant impacts (p < 0.05). Conclusion: The oral health, age, presence of pain and chronic disease of individuals had significant influence on health-related quality of life.
Keywords: Oral health; General health; Quality of life; Oral health surveys